Non-neural phenotype of spinal and bulbar muscular atrophy: results from a large cohort of Italian patients. Issue 8 (26th October 2015) - Querin, Giorgia; Bertolin, Cinzia; Da Re, Elisa; Volpe, Marco; Zara, Gabriella; Pegoraro, Elena; Caretta, Nicola; Foresta, Carlo; Silvano, Maria; Corrado, Domenico; Iafrate, Massimo; Angelini, Lorenzo; et al.
Abstract : Objective: To carry out a deep characterisation of the main androgen-responsive tissues involved in spinal and bulbar muscular atrophy (SBMA). Methods: 73 consecutive Italian patients underwent a full clinical protocol including biochemical and hormonal analyses, genitourinary examination, bone metabolism and densitometry, cardiological evaluation and muscle pathology. Results: Creatine kinase levels were slightly to markedly elevated in almost all cases (68 of the 73; 94%). 30 (41%) patients had fasting glucose above the reference limit, and many patients had total cholesterol (40; 54.7%), low-density lipoproteins cholesterol (29; 39.7%) and triglyceride (35; 48%) levels above the recommended values. Although testosterone, luteinising hormone and follicle-stimulating hormone values were generally normal, in one-third of cases we calculated an increased Androgen Sensitivity Index reflecting the presence of androgen resistance in these patients. According to the International Prostate Symptom Score (IPSS), 7/70 (10%) patients reported severe lower urinal tract symptoms (IPSS score >19), and 21/73 (30%) patients were moderately symptomatic (IPSS score from 8 to 19). In addition, 3 patients were carriers of an indwelling bladder catheter. Videourodynamic evaluation indicated that 4 of the 7 patients reporting severe urinary symptoms had an overt prostate-unrelated bladder outlet obstruction. Dual-energy X-ray absorptiometry scan data were consistent with low bone mass in 25/61 (41%) patients. Low bone mass was more frequent at the femoral than at the lumbar level. Skeletal muscle biopsy was carried out in 20 patients and myogenic changes in addition to the neurogenic atrophy were mostly observed. Conclusions: Our study provides evidence of a wide non-neural clinical phenotype in SBMA, suggesting the need for comprehensive multidisciplinary protocols for these patients.